2005
DOI: 10.1111/j.1439-0531.2005.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Posterior Pituitary Extract Stimulates Prolactin Release from the Anterior Pituitary Gland In Vitro and In Vivo in Cattle

Abstract: It has been reported that the posterior pituitary (PP) gland contains a potent, unknown prolactin (PRL)-releasing factor (PRF) in rats. PRFs are assumed to be produced in neurones located within the hypothalamus, and to be peptidergic in nature. However, little is known about PRFs in domestic animals. To characterize the PRF in the PP of domestic animals, the present study examined the PRL-releasing activity of an acidic extract from bovine PP (bPP) in vitro and in vivo in cattle. First, the PRL-releasing effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…These evidences suggest that PrRP might regulate PRL release from the anterior pituitary in rats which is still debatable, and that PrRP is unlikely to be an important regulator of PRL release in sheep. In cattle, PrRP failed to stimulate PRL release from anterior pituitary cell cultures, and intravenously administered PrRP failed to increase plasma PRL concentrations (Hashizume et al . 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These evidences suggest that PrRP might regulate PRL release from the anterior pituitary in rats which is still debatable, and that PrRP is unlikely to be an important regulator of PRL release in sheep. In cattle, PrRP failed to stimulate PRL release from anterior pituitary cell cultures, and intravenously administered PrRP failed to increase plasma PRL concentrations (Hashizume et al . 2005).…”
Section: Discussionmentioning
confidence: 99%
“…(2002) suggested that PrRP is unlikely to be an important prolactin‐releasing factor in this species. In cattle, intravenously administered PrRP did not induce plasma PRL release (Hashizume et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“…TRH-induced hyperprolactinemia has been shown to last for at least 90 min with slightly decreasing tendency in castrated calves [19], but may have been shorter in the intact dogs, as after 120 min serum prolactin concentrations had almost decreased to basal levels. Whether or not this short prolactin rise is causally related to the slight but not significant decrease of the mean LH concentration 20 min after TRH is questionable and cannot be concluded from the present data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several other prolactin-stimulating factors have been reported, such as serotonin [13] and thyrotrophin-releasing hormone (TRH) [14][15][16][17][18]. In a recent study the strong prolactin stimulating effect of TRH was also demonstrated in cattle in vitro and in vivo when compared with the prolactin release induced by a bovine posterior pituitary extract and prolactin releasing peptide [19]. Nevertheless, the exact role of TRH in the physiological regulation of prolactin secretion and the effect of the dopaminergic tone on TRH-induced prolactin secretion are not completely understood [7].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo , intravenous (IV) injection of PrRP-31 induces PRL release dependent on the estrus cycle and estrogen in rats (67, 68). On the other hand, IV injection of PrRP has no effect on PRL secretion in cattle (69), while intracerebroventricular (ICV) injection of PrRP temporarily increases PRL secretion (60). In addition to this, neither IV nor ICV injections induce PRL secretion in female sheep (43), suggesting that PrRP is not important in stimulating PRL secretion in ruminants.…”
Section: Biological Actions Of Prrp and Prrp2mentioning
confidence: 99%